Pemanfataan TikTok Sebagai Media Informasi Media Massa - Yoga, M. Sultan Prawira (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
TikTok is one of the fastest growing social media in the world. TikTok also allows users to create short 15-second videos with music, filters and other creative features. The theory used is New Media Pierre Levy, which explains the development of a new media. The research method in this research is descriptive qualitative. The results of the study show, (1) strategies for disseminating information through social media TikTok; (2) the process that occurs in the dissemination of information and the steps taken by AyoBandung.com in disseminating information via TikTok; (3) obstacles that occur during the dissemination of information through the TikTok AyoBandung.com social media account